Amyloid β Oligomers Disrupt Blood–CSF Barrier Integrity by Activating Matrix Metalloproteinases - Brkic, Marjana (J Neurosci, 2015)
The blood–CSF barrier (BCSFB) consists of a monolayer of choroid plexus epithelial (CPE) cells that maintain CNS homeostasis by producing CSF and restricting the passage of undesirable molecules and pathogens into the brain. Alzheimer's disease is the most common progressive neurodegenerative disorder and is characterized by the presence of amyloid β (Aβ) plaques and neurofibrillary tangles in the brain. Recent research shows that Alzheimer's disease is associated with morphological changes in CPE cells and compromised production of CSF. Here, we studied the direct effects of Aβ on the functionality of the BCSFB. Intracerebroventricular injection of Aβ1–42 oligomers into the cerebral ventricles of mice, a validated Alzheimer's disease model, caused induction of a cascade of detrimental events, including increased inflammatory gene expression in CPE cells and increased levels of proinflammatory cytokines and chemokines in the CSF. It also rapidly affected CPE cell morphology and tight junction protein levels. These changes were associated with loss of BCSFB integrity, as shown by an increase in BCSFB leakage. Aβ1–42 oligomers also increased matrix metalloproteinase (MMP) gene expression in the CPE and its activity in CSF. Interestingly, BCSFB disruption induced by Aβ1–42 oligomers did not occur in the presence of a broad-spectrum MMP inhibitor or in MMP3-deficient mice. These data provide evidence that MMPs are essential for the BCSFB leakage induced by Aβ1–42 oligomers. Our results reveal that Alzheimer's disease-associated soluble Aβ1–42 oligomers induce BCSFB dysfunction and suggest MMPs as a possible therapeutic target. SIGNIFICANCE STATEMENT No treatments are yet available to cure Alzheimer's disease; however, soluble Aβ oligomers are believed to play a crucial role in the neuroinflammation that is observed in this disease. Here, we studied the effect of Aβ oligomers on the often neglected barrier between blood and brain, called the blood–CSF barrier (BCSFB). This BCSFB is formed by the choroid plexus epithelial cells and is important in maintaining brain homeostasis. We observed Aβ oligomer-induced changes in morphology and loss of BCSFB integrity that might play a role in Alzheimer's disease progression. Strikingly, both inhibition of matrix metalloproteinase (MMP) activity and MMP3 deficiency could protect against the detrimental effects of Aβ oligomer. Clearly, our results suggest that MMP inhibition might have therapeutic potential.